Polymicrobial bacteremia and Strongyloides hyperinfection syndrome: Vigilance in patients on corticosteroids. (2022) - Boyle, Evan; Coppock, Dagan
Abstract: Strongyloidiasis is a worldwide parasitic infection. Many who develop infection remain asymptomatic. Due to Stronygloides autoinfection cycle it can result in chronic infection over decades. Immunosuppression particularly with corticosteroids has been associated with a rapid acceleration of the autoinfection cycle known as Strongyloides hyperinfection syndrome. The hyperinfection syndrome has severe complications and is associated with significant patient mortality. Here we report a case of hyperinfection complicated by polymicrobial bacteremia and intestinal ileus and review the literature regarding the hyperinfection syndrome.